Open formulation of strategy using collective intelligence by enterprises - Urbanowska-Sojkin, Elżbieta; Weinert, Adam (Zarządzanie strategiczne w dobie cyfrowej gospodarki sieciowej, 2020)
The issues discussed in the article concern contemporary challenges in the area of strategic management, and in particular the issue of strategic openness, manifested, inter alia, in the process of formulating the strategy, commonly referred to as the Open Strategy. The theoretical foundations of the new concept of strategic management point to the importance of various factors for an open process, including primarily Collective Intelligence conditioning strategic choices, their implementation and efficiency. The aim of the article is to establish a conceptual framework for an open strategy supported by collective co-creation and to present the results of applications in enterprises in Polish conditions. Preliminary empirical results show that the Open Strategy concept is still relatively poorly recognized among the respondents, and in the surveyed enterprises the approach characterized by a closed strategy formulation process focused only on the main strategies within the organization dominates. Therefore, further research questions arise about determining the causes and perspectives of an open strategy.